2017
DOI: 10.4235/agmr.2017.21.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Korean Version of Physical Activity Scale for the Elderly and International Physical Activity Questionnaire-Short Form in Evaluation of Frailty Phenotype

Abstract: Background: Evaluation of frailty in older people requires assessment of their physical activity level. The Korean version of the Physical Activity Scale for the Elderly (K-PASE) questionnaire is more comprehensive, yet it can be time-consuming and costly to administer on a large scale. The International Physical Activity Questionnaire (IPAQ) short form, which is simpler and free of charge, may replace the K-PASE for defining the Cardiovascular Health Study (CHS) frailty phenotype. Methods: We analyzed data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The Aging Study of PyeongChang Rural Area (ASPRA) is a population-based cohort study for frailty and geriatric syndromes in older adults living in a rural area. Detailed information on study design, target population, and measurements in ASPRA were described previously [3,18]. Participants who are living in PyeongChang County, Gangwon Province, Korea, were enrolled and annually administered comprehensive geriatric assessments including medical, physical, and psychosocial status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aging Study of PyeongChang Rural Area (ASPRA) is a population-based cohort study for frailty and geriatric syndromes in older adults living in a rural area. Detailed information on study design, target population, and measurements in ASPRA were described previously [3,18]. Participants who are living in PyeongChang County, Gangwon Province, Korea, were enrolled and annually administered comprehensive geriatric assessments including medical, physical, and psychosocial status.…”
Section: Methodsmentioning
confidence: 99%
“…The Cardiovascular Health Study (CHS) scale was used to measure physical frailty [19]. This scale assigns 1 point to each of the following five components: (1) exhaustion (“moderate or most of the time during the past week” to either of the following statements, “I felt that everything I did was an effort” or “I could not get going”); (2) low activity (lowest quintile in physical activity level measured using the International Physical Activity Questionnaire Short Form [18,20]); (3) slowness (usual gait speed <0.8 m/s from the 4-m walk test); (4) weakness (dominant hand grip strength <26 kg for men and <17 kg for women); and (5) weight loss (unintentional weight loss >3 kg during the previous 6 months). Individuals were classified as robust if the score was 0, prefrail if 1–2, and frail if 3–5.…”
Section: Methodsmentioning
confidence: 99%
“…The population of this study was analyzed from the Aging Study of Pyeongchang Rural Area (ASPRA), a population-based, prospective cohort study of frailty and geriatric syndromes that has covered 1,650 community-dwelling, older adults since December 2014 [ 16 ]. The detailed design and method of ASPRA have been described elsewhere [ 16 , 17 ]. Briefly, older adults residing in Pyeongchang County, Gangwon Province, Korea, located 180 km east of Seoul, were enrolled through public healthcare networks.…”
Section: Methodsmentioning
confidence: 99%
“…A Korean study found moderate to high agreement between the CHS frailty phenotype definitions based on the K-PASE or International Physical Activity Questionnaire short form. 27) In this context, subjects with three or more components were considered to have physical frailty.…”
Section: Assessment Of Fried's Physical Frailty Phenotypesmentioning
confidence: 99%